Paediatric nail consultation in an academic centre in Belgium: a 10‐year retrospective study. (27th March 2019) - Tasia, M.; Lecerf, P.; Richert, B.; André, J.
Abstract: Background: Very few studies have been conducted to establish the nature and prevalence of nail disorders in children. Objectives: To determine the frequency of various nail conditions in the paediatric setting and to report their management and follow‐up. Methods: This was a retrospective study between 2007 and 2017 of children under 18. All the patients were evaluated in our paediatric nail clinic at the dermatology department of Queen Fabiola Children's University Hospital. The data were synthesized from information obtained through medical records as well as from photographs taken during consultation. Follow‐up was completed by phone interview. Results: Three hundred and one patients were included. The majority of nail abnormalities involved the toenails (57.6%). The most common clinical signs were, in descending order, Beau's lines, pachyonychia, subungual hyperkeratosis and onycholysis. The most frequent diagnoses were fever‐related Beau's lines or onychomadesis (9.7%), trachyonychia (8.4%), longitudinal melanonychia (8.1%) and congenital malalignment of the great toenail (8.1%). The main diagnoses by age group were as follows: congenital hypertrophy of the lateral nail folds (21.4%) [0–2 years old]; fever‐related Beau's lines or onychomadesis (21%) [2–6 years old]; trachyonychia (22%) [6–12 years old]; and juvenile ingrown nail (21.4%) [12–18 years old]. Management included clinical observation for 119 patients and specific advices for 108 patients. A treatment was prescribed for 134 patients, topical in 76.5% of cases. Follow‐up demonstrated complete healing in 50.6% of patients and improvement in 19.7%. Conclusion: The most frequent nail disorders are benign, and their distribution varies with age. Management mainly involves conservative care, and the prognosis is favourable in the majority.